2019
DOI: 10.2147/jmdh.s189461
|View full text |Cite
|
Sign up to set email alerts
|

<p>Health care professionals&rsquo; knowledge and awareness of the ICD-10 coding system for assigning the cause of perinatal deaths in Jordanian hospitals</p>

Abstract: Objectives There is a lack of studying vital registration and disease classification systems in low- and middle-income countries. This study aimed to assess health care professionals’ (HCPs’) level of awareness, knowledge, use, and perceived barriers of the International Classification of Diseases, 10th version (ICD-10) as well as their perceptions of the electronic neonatal death registration system. Participants and methods A mixed method approach including descriptiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…The rate is higher than the rate of 7.81 per 1000 births that was reported in a multi-ethnic Middle-Eastern-based study [4] and the rates reported for the year 2015 for some other Arab countries, such as Libya (8.8 per 1000 live births), Oman (8.5 per 1000 live births), Qatar (5.8 per 1000 live births), and Kuwait (5.1 per 1000 live births) [11]. However, the rate was lower than the rate of 11.6 per 1000 live births that was reported in a previous Jordan study in 2012 [8] and the 2015 rates in other countries, such Syria (11.1), Saudia Arabia (13.9), Egypt (12.2), Iraq (15.5), and Jordan (10.5) [11]. This decline is promising and might be related to improvements in maternal health care services, yet there remains room for more improvement.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The rate is higher than the rate of 7.81 per 1000 births that was reported in a multi-ethnic Middle-Eastern-based study [4] and the rates reported for the year 2015 for some other Arab countries, such as Libya (8.8 per 1000 live births), Oman (8.5 per 1000 live births), Qatar (5.8 per 1000 live births), and Kuwait (5.1 per 1000 live births) [11]. However, the rate was lower than the rate of 11.6 per 1000 live births that was reported in a previous Jordan study in 2012 [8] and the 2015 rates in other countries, such Syria (11.1), Saudia Arabia (13.9), Egypt (12.2), Iraq (15.5), and Jordan (10.5) [11]. This decline is promising and might be related to improvements in maternal health care services, yet there remains room for more improvement.…”
Section: Discussionmentioning
confidence: 76%
“…The scarcity of data in Jordan on stillbirth is generally linked to the fact that stillbirths are not registered [8]. In addition, the existing sources of data on stillbirths are liable to biases.…”
Section: Introductionmentioning
confidence: 99%
“…The rate is higher than the rate of 7.81 per 1000 births that was reported in a multi-ethnic Middle-Eastern-based study (4) (11). However, the rate was lower than the rate of 11.6 per 1000 live births that was reported in a previous Jordan study in 2012 (8) and the 2015 rates in other countries, such Syria (11.1), Saudia Arabia (13.9), Egypt (12.2), Iraq (15.5), and Jordan (10.5) (11). This decline is promising and might be related to improvements in maternal health care services, yet there remains room for more improvement.…”
Section: Discussionmentioning
confidence: 58%
“…The scarcity of data in Jordan on stillbirth is generally linked to the fact of that the stillbirths are not registered (9). In addition, the existing sources of data on stillbirths are liable to biases.…”
Section: Introductionmentioning
confidence: 99%